Large Terrestrial Bird Adapting Behavior in an Urbanized Zone - Eduardo R. Alexandrino; Juliano A. Bogoni; Ana B. Navarro; Alex A. A. Bovo; Rafael M. Gonçalves; Jacob D. Charters; Juan A. Domini; Katia M. P. M. B. Ferraz (Animals, 2019)
Wildlife living within urban ecosystems have to adapt or perish. Red-legged Seriema, a large terrestrial bird, are rare in urban ecosystems, however, they have been reported in a medium-sized Brazilian city. We investigated the reasons for this occurrence as well as their behavior. We assessed the distribution of Seriemas (including fledglings), free-ranging cats, and cat-feeding points provided by humans, and past records of Seriemas in the study area. We discovered that Seriemas are sharing spatial resources with cats without apparent conflicts, and intraspecific competition was important to define the spatial distribution of Seriemas. This species is able to use human-made structures to improve territory defense and opportunistic foraging. Direct and indirect human food provisioning is helping them to survive in the studied area, but is also facilitating the domestication process, which may cause future conflicts with humans and cats. Although Seriemas have inhabited the studied urban area for years, they are still adapting their behaviors for urban life, as they have not yet perceived the dangers of automotive traffic. Our study corroborates that wild species may adapt to urban areas driven by human contact, but it also acts as a trap for the adaptive process.